In vitro assessment of probiotic and functional properties of Bacillus coagulans T242. (August 2020) - Sui, Lin; Zhu, Xuemei; Wu, Danyang; Ma, Tian; Tuo, Yanfeng; Jiang, Shujuan; Qian, Fang; Mu, Guangqing
Abstract: Bacillus coagulans T242 has high lactase-producing activity and the lactase produced is thermally stable. However, the probiotic and other functional properties of the bacterium had not been studied and the bacterium needed further investigation for potential use in food products. This study aimed to evaluate the probiotic and functional characteristics of B. coagulans T242 in vitro . B. coagulans T242 has a high resistance to simulated gastric juice (pH 3.0) and bile salt (0.3%), indicating that it may have a good tolerance of gastrointestinal conditions. The adhesion of B. coagulans T242 to HT-29 cells was calculated as 58%. Additionally, B. coagulans T242 reduced the adhesion of Escherichia coli to HT-29 cells by up to 62%. B. coagulans T242 is sensitive to amoxicillin, amikacin, tetracycline, chloramphenicol, and rifampin, and is moderately sensitive to ciprofloxacin and erythromycin. These characteristics showed that B. coagulans T242 is a potential probiotic bacterium. B. coagulans T242 showed good cholesterol assimilation potential (19.9%) in vitro . In addition, B. coagulans T242 showed a high capacity for scavenging 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radicals (35.0%), hydroxyl radicals (39.0%), and superoxide anion radicals (14.8%), and good reducing power (58.5 μmol/L ascorbic acid equivalent). It was speculated that B. coagulans T242 might have the potential to exert antioxidant activity in vitro . These preliminary results suggested that B. coagulans T242 has the potential to be used as a probiotic.